Population collapse dynamics in Acropora downingi, an Arabian/Persian Gulf ecosystem‐engineering coral, linked to rising temperature. (10th April 2018) - Riegl, Bernhard; Johnston, Matthew; Purkis, Sam; Howells, Emily; Burt, John; Steiner, Sascha C. C.; Sheppard, Charles R. C.; Bauman, Andrew
Abstract: As in the tropical Atlantic, Acropora populations in the southern Persian/Arabian Gulf plummeted within two decades after having been ecosystem engineers on most wave‐exposed reefs since the Pleistocene. Since 1996/1998 live coral cover in the Gulf declined by over 90% in many areas, primarily due to bleaching and diseases caused by rising temperatures. In the formerly dominant table‐coral species A. downingi, population dynamics corresponding to disturbance regimes was quantified in three transition matrices (lower disturbance pre‐1996; moderate disturbance from 1998 to 2010 and 2013 to 2017, disturbed in 1996/1998, 2010/11/12, 2017). Increased disturbance frequency and severity caused progressive reduction in coral size, cover, and population fecundity. Small size‐classes were bolstered more by partial colony mortality than sexual recruitment. Some large corals had a size refuge and resisted die‐back but were also lost with increasing disturbance. Matrix and biophysical larval flow models suggested one metapopulation. Southern, Arabian, populations could be connected to northern, Iranian, populations but this connectivity was lost under assumptions of pelagic larval duration at rising temperatures shortened to a third. Then, the metapopulation disintegrated into isolated populations. Connectivity required to avoid extinctions increased exponentially with disturbance frequency and correlation of disturbances across the metapopulation. Populations became unsustainable at eight disturbances in 15 years, when even highest theoretical recruitment no longer compensated mortality. This lethal disturbance frequency was 3‐fold that of the moderately disturbed monitoring period and 4‐fold of the preceding low‐disturbance period—suggesting ongoing shortening of the disturbance‐free period. Observed population collapse and environmental changes in the Gulf suggest that A. downingi is heading toward at least functional extinction mainly due to increasingly frequent temperature‐induced mortality events, clearly linked to climate change. Abstract : Population dynamics of a formerly dominant ecosystem engineer in the Persian/Arabian Gulf, the reef coral Acropora downingi, changed over the past three decades. Responsible are increasingly frequent disturbance by heat, that cause widespread and severe mortality. Populations are increasingly dominated by corals in smaller size‐classes and are less fertile. Connectivity in the metapopulation is declining. The undisturbed period between disturbances has been reduced in length to only a quarter of that observed from the 1960s to 1990s and is fast approaching a theoretical extinction threshold.